Structural material nuclear data basic research - Avrigeanu, Marilena; Avrigeanu, Vlad (Frontiers in Physics, 2023)
The nuclear–data evaluation for deuteron–induced reactions and α-particle emission by neutron interactions is addressed within the Research Topic on Nuclear data for fusion technology, from basic research to full-scale applications. They are open issues in the area of nuclear data for fusion technology, specifically for nuclear design of the ITER fusion device, the European DEMO fusion reactor, and the IFMIF-DONES irradiation facility. High-quality cross-section data for reactions induced by neutrons and deuterons are thus required in the energy range up to 50 MeV. While the TENDL evaluated nuclear data library, based on the output of the TALYS nuclear model code system, has gained a world-wide use in basic research as well as applications including nuclear fusion technology, a need of its further improvement has recently been pointed out. Because in comparison to fission applications, both the energy range and the diversity of nuclear data for fusion technologies are by far broader, specific nuclear data evaluations are concerned to improve the TENDL files based on calculations with the TALYS code. Consequently, the progress of nuclear data activities conducted more recently on deuteron–induced reactions and α-emission by neutron interactions, throughout the European Fusion Programme and subsequent to previous achievements within F4E and EUROfusion programmes, is briefly reviewed.